Distinct immune sensor systems for fungal endopolygalacturonases in closely related Brassicaceae - Zhang, Lisha; Hua, Chenlei; Pruitt, Rory N.; Qin, Si; Wang, Lei; Albert, Isabell; Albert, Markus; Van Kan, Jan A. L.; Nuernberger, Thorsten (Nature Plants, 2021)
Plant pattern recognition receptors (PRRs) facilitate recognition of microbial patterns and mediate activation of plant immunity. Arabidopsis thaliana RLP42 senses fungal endopolygalacturonases (PGs) and triggers plant defence through complex formation with SOBIR1 and SERK co-receptors. Here, we show that a conserved 9-amino-acid fragment pg9(At) within PGs is sufficient to activate RLP42-dependent plant immunity. Structure–function analysis reveals essential roles of amino acid residues within the RLP42 leucine-rich repeat and island domains for ligand binding and PRR complex assembly. Sensitivity to pg9(At), which is restricted to A. thaliana and exhibits scattered accession specificity, is unusual for known PRRs. Arabidopsis arenosa and Brassica rapa, two Brassicaceae species closely related to A. thaliana, respectively perceive immunogenic PG fragments pg20(Aa) and pg36(Bra), which are structurally distinct from pg9(At). Our study provides evidence for rapid evolution of polymorphic PG sensors with distinct pattern specificities within a single plant family.
CRIS-Team Scopus Importer:2021-08-13